Strategi Pemasaran Dengan Memanfaatkan Media Sosial Sebagai Alat Promosi Guna Meningkatan Pemasaran Secara Global - Riyani Sijabat; Feby Caroline; Benget Marcelino Sitinjak; Lenti Susanna Saragih; Aurora Elise Putriku (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
In the modern era, advancements in technology and information have transformed traditional communication into digital formats. Companies leverage technology to compete and survive in a competitive environment. Social media plays a crucial role in interaction, information exchange, and collaboration, serving as a powerful business promotion tool due to its broad reach. In global marketing, companies must develop creative and adaptive strategies to utilize social media effectively. This study employs a qualitative descriptive method to identify the success factors of marketing strategies using social media in a global context. The findings indicate that global marketing strategies require a deep understanding of target markets, positioning, marketing mix, and budgeting, as well as adaptation to cultural, economic, and legal factors in the target markets.